Improving dielectric strength of polyvinylidene fluoride by blending chains with different molecular weights. (2nd March 2020) - Fan, Benhui; Xing, Zhaoliang; Bedoui, Fahmi; Yuan, Jinkai; Lu, Xiaoxin; He, Delong; Zhou, Mingyu; Zhang, Chong; Dang, Zhimin; Weigand, Steven; Bai, Jinbo
Abstract: Polyvinylidene fluoride (PVDF), as an electroactive polymer, has been attracting increasingly attention for its broad potential applications ranging from film capacitors, actuators, to energy harvesters. The capability of a PVDF film to sustain a high working voltage is highly demanded to achieve these applications. Herein, we find that blending two PVDF polymers with low and high molecular weights can achieve higher dielectric strength (Eb = 479 MV/m) than either of the two original ones (PVDF-1 with Mw of 180, 000, Eb = 412 MV/m and PVDF-2 with Mw of 441, 000, Eb = 391 MV/m). The underlying synergetic effect is deduced from the analysis of the crystallization of PVDF by wide-angle X-ray diffraction and small-angle X-ray scattering from a synchrotron source. It involves crystallite polymorphism, the transition of crystalline phases, the variation of crystalline lattice spacing at different strain spaces, and the long periods and the distribution of crystallite sizes. Understanding these underlying influences is beneficial to process PVDF films with desirable and reliable dielectric properties. Graphical abstract: Image 1 Highlights: The capability of a polyvinylidene fluoride (PVDF) film to sustain a high working voltage is highly demanded to achieve the applications such as film capacitors, actuators, to energy harvesters. Blending PVDF of high and low Mw improves the breakdown strength of the film. The synergetic effect is associated with the crystallization. The underlying synergetic effect is deduced from the analysis of the crystallization of PVDF by wide-angle X-ray diffraction and small-angle X-ray scattering from a synchrotron source. It involves crystallite polymorphism, the transition of crystalline phases, the variation of crystalline lattice spacing at different strain spaces, and the long periods and the distribution of crystallite sizes.